Anthropometric Analysis Between Naso Aural Inclination and Their Correlation in Bangladeshi Buddhist Rakhain Ethnic Females (Journal of Current and Advance Medical Research, 2023)
Background: There is no available anthropometric data on the facial features of the Rakhain population of Bangladesh.Objective: The aim of the study was to describe a standard of normative facial anthropometric values related to the facial height of adult healthy Bangladeshi Buddhist Rakhain females.Methodology: This cross-sectional observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2011 to December 2011 for a period of one (01) year. Adult healthy Bangladeshi Buddhist Rakhain females in the age group of 18 to 30 years were included as the study population. The standard of normative facial anthropometric values related to facial heights were measured by upper facial height (UFH) and lower facial height (LFH).Results: A total number of 100 adult healthy Bangladeshi Buddhist Rakhain females were recruited for this study. The mean with SD of LFH was 56.40(±5.49) and the mean with SD of UFH was 46.68(±3.34). LFH was significantly greater than UFH.Conclusion: In conclusion, the standard of normative facial anthropometric values related to LFH is significantly greater than UFH among the adult healthy Bangladeshi Buddhist Rakhain females.Journal of Current and Advance Medical Research, January 2023;10(1):31-34